Pembuatan Prototipe Pangkalan Data Direktori Indonesianis Menggunakan SLiMS Cendana - ., Rudianto; Rachmaniah, Meuthia; Basuki, Sulistyo (Perpustakaan IPB, 2015)
Directory of Indonesianist is one of the reference collections that a library must provide. Only a few libraries provide it. The second fact is the directory of Indonesianist is an old publication that never has a new version. This directory is printed material and limited edition, it makes the library-user difficult to find the Indonesianist data. Until this time, there is no one of directory of Indonesianist administered online. This research purposed to build an online web based directory of Indonesianist database by using SLiMS Cendana. This research has five steps: (1) preliminary investigation; (2) choosing the sample of Indonesianist data and publication using googlescholar, scholarometer and googlebooks; (3) studying SLiMS, (4) making a prototipe based on study about SLiMS in the previous step; (5) examination of the recall and precision of the